Перша міжнародна конференція “Водорості в наземних екосистемах” (27-30 вересня 2005 року, Канів) - Кондратюк, С.Я.; Костіков, І.Ю.; Михайлюк, Т.І.; Дарієнко, Т.М.; Демченко, Е.М. (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Перша міжнародна конференція “Водорості в наземних екосистемах” (27-30 вересня 2005 року, Канів)